The Legal Efforts to Maintain the Authenticity of Trade Secrets through a License Agreement (Journal of Private and Commercial Law, 2019)
A trade secret is part of IPR which the information is not known by the general public in the field of technology and business, in trade secret has economic and useful values in business activities, also maintain confidential by the owner of the trade secrets regulated by the Law No.30 of 2000. The parties can use trade secret and license agreements, license is the permit given by the owner of trade secrets to other parties through agreements on granting the right to get economic benefits for a certain period of time. The advantage of IPR is personal wealth that can be owned and treated with other wealth forms. The legal research method used in this study is to use a normative juridical approach, which means that a study is conducted based on the review of laws. The efforts to protect trade secrets begin with binding provisions for employees based on the employment agreement, and the licensing agreement. In order to be protected by the trade secret the information must be totally confidential, because if the information has revealed the protection will be lost, the information will become public property. For dispute resolution, litigation and non-litigation can be taken according to the needs of the parties.